Resistance to propagation of amygdaloid kindling seizures in rats with genetic absence epilepsy - ONAT, FİLİZ; GÜLHAN, REZZAN (BLACKWELL PUBLISHING INC, 2002)
Purpose: The existence of absence epilepsy and temporal partial seizure pattern in the same patient is an uncommon state. In the present study, we aimed to evaluate whether the process of kindling as a model of complex partial seizures with secondary generalization is altered in rats with genetic absence epilepsy. Methods: Six- to 12-month-old nonepileptic control Wistar rats and genetic absence epileptic rats from Strasbourg (GAERS) were used in the experiments. One week before the experiments, bilateral stimulation and recording electrodes were implanted stereotaxically into the basolateral amygdala and cortex, respectively. Animals were stimulated at their afterdischarge threshold current twice daily for the process of kindling and accepted as fully kindled after the occurrence of five grade 5 seizures. Bilateral EEGs from amygdala and cortex were recorded continuously during 20 min before and 40 min after each stimulus. Results: All control Wistar rats were fully kindled after stimulus 12 to 15. Although the maximal number of stimulations had been applied, GAERS remained at stage 2, and no motor seizures were observed. The afterdischarge duration in bilateral amygdala and the cortex after the kindling stimulus was shorter in GAERS when compared with control rats. Conclusions: Occurrence of only grade 2 seizures and no observation of grade 3-5 seizures in GAERS with the maximal number of stimulations would suggest that the generalized absence seizures may be the reason of the resistance in the secondary generalization of limbic seizures during amygdala kindling.
Keywords: absence; partial seizures; GAERS; kindling; rat; TEMPORAL-LOBE; MECHANISMS; ENHANCEMENT; VIGABATRIN; DISORDERS